2000
DOI: 10.1021/ic991165f
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Coordinating Anions HA2-Generated from Oxoanions A-and Their Conjugate Acids. Coordination Equilibria, Ionic Conductivities, and the Structures of {Cu2(H(CH3SO3)2)4}nand [Cu(CO)(H(CF3CO2)2)]2

Abstract: The coordination or ion pairing of the hydrogen-bonded anions H(CF3CO2)2- and H(CH3SO3)2- to NEt4+, Li+, Cu+, and/or Cu2+ was investigated. The structure of [Cu2(H(CH3SO3)2)4]n consists of centrosymmetric dimeric moieties that contain two homoconjugated (CH3SO2O-H...OSO2CH3)- anions per Cu2+ ion, forming typical Jahn-Teller tetragonally elongated CuO6 coordination spheres. The oxygen atoms involved in the nearly linear O-H...O hydrogen bonds (O...O approximately 2.62 A) are not coordinated to the Cu2+ ions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…CO p-backbonding. The measured IR absorptions are in agreement with the data previously reported for a compound of the [Cu(O 2 CCF 3 )(CO)] composition by Rodesiler and Amma (2120 cm -1 in an unspecified medium [3a]), Pampaloni (2130 cm -1 in nujol mulls [5a]), and Strauss (2136 cm -1 in fluorolube mulls [4]). …”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…CO p-backbonding. The measured IR absorptions are in agreement with the data previously reported for a compound of the [Cu(O 2 CCF 3 )(CO)] composition by Rodesiler and Amma (2120 cm -1 in an unspecified medium [3a]), Pampaloni (2130 cm -1 in nujol mulls [5a]), and Strauss (2136 cm -1 in fluorolube mulls [4]). …”
Section: Resultssupporting
confidence: 89%
“…The structure of 1 consists of dicopper(I,I) units cis-bridged by two trifluoroacetate groups and also containing one carbonyl ligand at each copper(I) center, [Cu 2 (m 2 -O 2 CCF 3 ) 2 (CO) 2 ]. This contrasts to the previously suggested tetranuclear structure assigned to 1 in [5a] but is consistent with the dinuclear core found in the trifluoroacetic acid bisadduct, [Cu 2 (O 2 CCF 3 ) 2 (CO) 2 (HO 2 CCF 3 ) 2 ] (2) [4].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The relationship between acidity and mole fraction of the acids (for the regime where the dominant factor is the anion combination with free acid,0 .5 < c < 1, to form hydrogen bondedd ianions and clusters [A(HA) x ] À ) [54,61] needs more explanation. This association of the free acid and the anion lowers the basicity of the counterion as explained by Polyakov et al [62] It was shown in ar ecent communication [53] that H 0 values of ah ydrogen sulfate ionic liquid's mixtures with H 2 SO 4 changes linearly with mole ratio of the acid over almost the full range of compositions. The same behavior can be assumed for DMI hydrogen sulfate and methanesulfonate PILs so it can be concludedt hat 13 Cc hemical shift of DMI after protonation changes linearly with acidity.T he similar slopes of the fitted lines (À11.5 for H 2 SO 4 and À11.0 for HOMs), seen in Figure 5, show as imilare ffect of anion combination with free acids on their basicities for the two cases.…”
Section: Resultsmentioning
confidence: 85%